“Estudio constructivo estabilización de taludes Con hormigón lanzado, malla electro soldada y Pernos de anclaje de concreto reforzado, caso: Ventana del túnel auxiliar Sara yunga-gramalote, Que conecta al túnel de conducción-chimenea de Equilibrio, del proyecto minas-San Francisco” - Ayala Encalada, Byron Omar (Machala, 2015)
Ayala Encalada B.O. (2015) “Estudio constructivo estabilización de taludes Con hormigón lanzado, malla electro soldada y Pernos de anclaje de concreto reforzado, caso: Ventana del túnel auxiliar Sara yunga-gramalote,Que conecta al túnel de conducción-chimenea de Equilibrio, del proyecto minas-San Francisco” (Tesis de Pregrado) UTMACHALA, Unidad Academica de Ingenieria Civil, Machala, Ecuador
The main objective of slope stabilization is to establish prevention and control measures to prevent or avoid any risk or threat in an area of ​​questionable stability.      Anchor bolts and shotcrete are a means Ensure the stability of slopes and slopes, can be used in any situation in which the stability of a solid to withstand different states of stress or strain will see necessary.      Furthermore, this type of support counteracts the sub-pressures produced by the water, which is widely used for different types of work in the maintenance of tunnels and mining, hydroelectric, on slopes consisting mass of soil and / or rocks .      Sarayunga is located in an area where it is common to the landslide by excessive rainfall and soil moisture. So it was necessary to find a method to avoid these slides so that people working around are protected and there is no damage.      The method proposed in this case is the most useful, economical, fast in its running and provides security from the start unlike other methods that provide security until they are finished. It also gives ease of construction process reliability flange for resistance and use.
Keywords: TALUDES; HUMEDAD DEL SUELO